Novel insights into the nanoadsorption mechanisms of crystal violet using nano-hazelnut shell from aqueous solution - Mashael A. Al-Ajji (17191396) (2021)
This paper discusses the nanoadsorption mechanisms of crystal violet (CV) using a nano-hazelnut shell (nano-HS) from an aqueous solution. The effect of various factors such as pH, temperature, and initial CV concentration on the adsorption process was also evaluated. The physical and chemical characterizations of hazelnut shells (HS) and nano-HS were studied using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and transmission electron microscope (TEM). Various functional groups including single bondOH, Cdouble bondO, Csingle bondH, and Csingle bondO were identified that are facilitated the CV sorption onto the adsorbents. Additionally, the SEM revealed the adsorbents as a heterogeneous structure with deep cavities and high porosity, which is thought to play a vital role in capturing and binding the CV ions onto the surface of the adsorbent. The optimum pH in this study was reported to be 10. While Langmuir isotherm was identified as the best-suited model to describe the adsorption process, with a 93% and 96% correlation coefficient for HS and nano-HS, respectively. 181.82 mg/g was the maximum adsorption capacity for HS and 294.12 mg/g for nano-HS at 45 °C. Additionally, the positive value of changes in enthalpy for HS (21.912 kJ/mol) indicated the reaction was endothermic while the negative value (−47.541 kJ/mol) for nano-HS signifies that the CV adsorption onto was an exothermic reaction. The Gibbs free energy was found to increase with smaller nanoparticle sizes. On the other hand, the effects of particle size on the enthalpy and the entropy were increased. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2021.102354